Peran Agen Laku Pandai Dalam Meningkatkan Transaksi Non Tunai Pada Sektor Mikro di Masa Pandemi - Deny Yudiantoro; Afif Nur Rahmadi (Universitas Kadiri, 2021)
This study aims to identify and describe the role of Agen Laku Pandai BRI called BRILink in increasing public awareness, especially entrepreneurs in the micro sector, to conduct cashless transactions during the Pandemic. This research is in the form of descriptive research using a qualitative approach and the method used is a case study. The research was conducted by direct observations and interviews with informants who are BRI’s Agen Laku Pandai and BRILink Agent Officers who are employees of BRI. Observations on BRILink Agents are carried out together with BRI Officers when monitoring the agent. The results of in-depth observations and interviews show that the existence of BRILink Agents in the midst of society is able to increase the literacy of rural communities, especially micro entrepreneurs, regarding banking products. In addition, the existence of a BRILink Agent can facilitate cashless transactions from micro-entrepreneurs during a pandemic, where all activities must be limited. BRILink Agent as the spearhead of BRI can increase the penetration and financial performance of BRI, especially in terms of raising funds and channeling financing through the micro financing segment. Agen Laku Pandai is an effort by the government through Bank Indonesia and Otoritas Jasa Keuangan to create financial inclusion in Indonesia.